A Super‐Stretchable and Highly Sensitive Carbon Nanotube Capacitive Strain Sensor for Wearable Applications and Soft Robotics. Issue 3 (7th October 2021) - Hu, Xiaoguang; Yang, Furui; Wu, Mengxi; Sui, Yu; Guo, Di; Li, Ming; Kang, Zhan; Sun, Jining; Liu, Junshan
Abstract: The study of flexible and stretchable strain sensors is growing rapidly owing to the demands for human motion detection, human–machine interaction, and soft robotics. However, super‐stretchable and highly sensitive strain sensors with high linearity and low hysteresis are especially lacking, which therefore limits the use of soft strain sensors in varied practical applications. The stretchability and sensitivity of the capacitive strain sensor are constrained by the material characteristics and structure of parallel plate capacitor (theoretical gauge factor [GF] is 1). To address these limitations, a super‐stretchable and highly sensitive capacitive strain sensor composed of two strips of wrinkled carbon nanotubes‐based electrodes separated by a tape dielectric, is presented. By integrating nanomaterials and wrinkled film structure, this device achieves a GF of 2.07 at 300% strain with excellent linearity and negligible hysteresis. This is the first type of capacitive strain sensors that can achieve super‐stretchability and sensitivity simultaneously. Additionally, the sensor has a fast signal response time of ≈80 ms, and good mechanical durability during 1000 stretching and releasing cycles. The authors demonstrate the use of this sensor as a versatile wearable device for human motion tracking, and as a smart real‐time monitoring device for soft pneumatic robots. Abstract : Introducing a prestretched capacitive strain sensor for wearable applications and soft robotics, the sensor can distinguish subtle movements under wearing conditions with ≈120% strain.